Non-isothermal crystallization kinetics of bismuth germanate glass-ceramics - Surapong Panyata (2018)
© 2017 Glass-ceramics containing bismuth germanate were fabricated using the conventional melt-quenching method. Glasses have been prepared from BiO1.5-GeO2-BO1.5ternary glass system by focusing on the region of 59 mol% BiO1.5: 23 mol% GeO2: 18 mol% BO1.5. The non-isothermal crystallizations kinetic were studied by thermal analysis at various heating rates of 5, 10, 15, 20 °C/min. The resulting glass was analyzed by using differential thermal analysis (DTA) for determining the crystallization temperature (Tp). Then, the prepared glass pieces were heat treated at Tp. The element composition analysis of the quenched glass performed by energy dispersive X-ray fluorescence (EDXRF) analysis. X-ray diffraction (XRD) was used to obtain the phase formation of the heat treated glass-ceramics. Physical properties and their morphologies of the obtained glass-ceramics were also investigated. This crystallization kinetic result can be used to evaluate the crystallization potential of the interesting glasses. In the non-isothermal kinetics process, the average (Ea) value was 302.95 ± 2.25 kJ/mol. The calculated value of the Avrami parameter (n) by using Ozawa equation was found to be 1.69 which indicated that the crystallization mechanism was diffusion control with a one-dimensional crystal growth.